A CASE STUDY ON THE NEEDS ANALYSIS OF VOCATIONAL MEDICAL LAB STUDENTS AT THE NIT: Received: 18th April 2024 Revised: 22nd May 2024 & 5th June 2024 Accepted: 30th April 2024 - Hemn Mohammed Ali Mahmood (PUPIL: International Journal of Teaching, Education and Learning, 2024)
This study examines the educational requirements and teaching methods for English for Specific Purposes (ESP) in vocational medical laboratory students at the National Institute for Technology (NIT). The study utilizes the Research and Development (R&D) approach to create and evaluate methods for instructional and non-instructional items. The Instructional Development Model created by Dick (1996) outlines the study process, emphasizing Analysis, Design, Development, Implementation, and Evaluation (ADDIE) tasks. Information was gathered from second-semester students in the Diploma Medical Lab Department in the academic year 2023/2024 through questionnaires and organized interviews with professors and students. The results, studied descriptively, emphasize the student’s learning needs and preferences, underscoring the significance of proficient English communication abilities for their future professions. The study emphasizes the importance of integrating creative and interactive teaching approaches, such as technology, to improve students’ English skills and prepare them for the workforce. The results provide useful information for educators creating English language courses customized for the particular requirements of vocational medical laboratory students.